Comparison of U.S. 4-year and community college librarians' perspectives on competencies, challenges, and educational preparation for the instructional role. (December 2022) - Wang, Ting; Lund, Brady D.; Widdersheim, Michael; Fay, Brendan
The purpose of this study is to explore and compare community (2-year) college librarians' perceptions of their competencies, challenges, and educational preparation with those of librarians at 4-year colleges. Researchers created survey questions based on previous studies and distributed the survey through online mailing lists. The survey results indicated that community college instructional librarians' responses were generally not statistically significantly different from 4-year university librarians in terms of what skills, traits, and educational needs were most prevalent. From the perspective of career challenges, community college instructional librarians cited marketing and changing perceptions/needs of content area faculty, while the librarians at 4-year universities cited burnout and class overload. These differences reveal the substantial challenge of preparing instructional librarians according to the types of libraries and instructional approaches.